2021
DOI: 10.2337/dc21-1380
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Nonattendance in a Nationwide Screening Program for Diabetic Retinopathy: A Register-Based Cohort Study

Abstract: The aim of the study was to identify factors associated with nonattendance in a Danish nationwide screening program for diabetic retinopathy among people with type 2 diabetes. RESEARCH DESIGN AND METHODSA retrospective observational study linking individual-level register data was performed. First, we compared characteristics of 156,878 people with type 2 diabetes divided into attenders and never-attenders on the basis of their screening history over a 6-year period. Second, we assessed 230,173 screening inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Patient disease awareness could be insufficient as reported by a study from Hong Kong [ 28 ]. Several studies [ 29 , 30 ] focus on reasons for non-attendance (dropouts and never attendance). An overview of the total screening attendance of the Danish diabetes population does not exist, as The Danish Registry of Diabetic Retinopathy only reports patients who have been screened and not the total diabetes population [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patient disease awareness could be insufficient as reported by a study from Hong Kong [ 28 ]. Several studies [ 29 , 30 ] focus on reasons for non-attendance (dropouts and never attendance). An overview of the total screening attendance of the Danish diabetes population does not exist, as The Danish Registry of Diabetic Retinopathy only reports patients who have been screened and not the total diabetes population [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the early 2000s, there has been robust uptake of DR screening programs worldwide, driving 2019 screening rates to >80% in the United Kingdom and >70% in Denmark (8,9). Screening rates in the United States are lower, with just 65% of individuals with diabetes undergoing annual DR screening in 2019 (10).…”
mentioning
confidence: 99%
“…This review found that patients who belong to "ethnic minorities" or "socio-economic deprived" groups were less likely to attend DR screening and repeated non-attendance was associated with a higher risk of VTDR [174]. This has been confirmed in the Danish population in two recent register studies [175,176]. Many studies which focus on screening attendance or non-attendance are register based, and do not specify whether non-attendants included are drop-outs or never attendants.…”
Section: Screening Schemesmentioning
confidence: 73%